NURSES' PERCEPTION ABOUT COMPREHENSIVE CARE TO PEDIATRIC ONCOLOGICAL PATIENTS DURING CHEMOTHERAPY TREATMENT.: N/A (Revista Interdisciplinar Pensamento Científico, 2021)
Introduction: Cancer represents a deadly disease, but among children patients has a greater chance of cure, but for the treatment to be effective can not be excluded that it will influence difficult moments in environments that can become stressful, painful, mutilating, invasive and with prolonged duration. Therefore, it is necessary to establish good care practices during the treatment period, especially among nurses, professionals who are closer to the patients and their families. Based on this, this research seeks to identify in the literature the perception of the nursing professional regarding the pediatric cancer patient, especially during chemotherapy treatment. Methodology: This research is a literature survey study, where an integrative literature review was conducted using the Google Academic database, through the descriptors: Comprehensive Care; Pediatric Oncology Patient; Nurses' Perception; and Chemotherapy Treatment. Results and Discussion: The selected researches point out that there are gaps in the undergraduate nursing courses that have been a great obstacle for the nurses' performance. As well as the relations established by the nursing professional in the care of the child with oncologic disease, include those with whom he lives in the daily care: the child itself, the family, the health team, etc. Another point, and that nursing professionals experience emotional distress as a result of the relationships of the bond established with the child and his family. It was also evidenced the need for psychological support to health professionals as well. Conclusion: Thus, it is essential that palliative care be addressed in the curricula of nursing courses. In addition, the nursing team needs to have a good work structure in general. Finally, it was noted the need for further research that can support the resolution of the needs pointed out in the research.
Keywords: Comprehensive Care; Pediatric Oncology Patient; Perception of Nurses; Chemotherapy Treatment.